2013
DOI: 10.1111/cobi.12062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oil‐Palm Plantations on Diversity of Tropical Anurans

Abstract: Agriculturally altered vegetation, especially oil-palm plantations, is rapidly increasing in Southeast Asia. Low species diversity is associated with this commodity, but data on anuran diversity in oil-palm plantations are lacking. We investigated how anuran biological diversity differs between forest and oil-palm plantation, and whether observed differences in biological diversity of these areas is linked to specific environmental factors. We hypothesized that biological diversity is lower in plantations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 46 publications
4
47
1
2
Order By: Relevance
“…Previous studies in regions outside the Neotropics have revealed severe declines in abundance and species richness in oil palm relative to forests (Fitzherbert et al ., ; Edwards et al ., ). For example, vertebrate species richness in oil palm tends to be less than half that of natural forest (Fitzherbert et al ., ; Danielsen et al ., ), with declines of 80% reported for birds (Koh & Wilcove, ; Edwards et al ., ; but see Faruk et al ., for smaller declines among anurans). Similar impacts have been documented for invertebrates, with 64% declines reported among ants (Fayle et al ., ) and 50% declines among dung beetles (Edwards et al ., ,b) in Malaysian Borneo.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in regions outside the Neotropics have revealed severe declines in abundance and species richness in oil palm relative to forests (Fitzherbert et al ., ; Edwards et al ., ). For example, vertebrate species richness in oil palm tends to be less than half that of natural forest (Fitzherbert et al ., ; Danielsen et al ., ), with declines of 80% reported for birds (Koh & Wilcove, ; Edwards et al ., ; but see Faruk et al ., for smaller declines among anurans). Similar impacts have been documented for invertebrates, with 64% declines reported among ants (Fayle et al ., ) and 50% declines among dung beetles (Edwards et al ., ,b) in Malaysian Borneo.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy sedimentation and siltation of streams from human-modified lands has affected populations of the critically endangered Chile Mountains False Toad (Telmatobufo venustus) and congeners, and ex-situ assurance colonies have been implemented to mitigate the effects of modified and lost habitat (Fenolio et al, 2011). Other studies show that human-modified tropical forests negatively affect anuran community composition and diversity (Faruk et al, 2013), and human intervention in freshwater ecosystems has been shown to fuel disease emergence (Peeler and Feist, 2011). Furthermore, Hof et al (2011) have shown how land modification in conjunction with pathogens and climate change will negatively affect amphibian diversity.…”
Section: Reviewsmentioning
confidence: 99%
“…Brühl and Eltz, 2009;Faruk et al, 2013;Woodcock et al, 2011), we expected there to be changes in the diet of the ant specialist toad P. juxtaspera. However, we found that interactions between these trophic levels remained relatively constant despite significant changes in the community composition of ants.…”
Section: Discussionmentioning
confidence: 99%
“…In this region, the important drivers of changes in community structure and function are logging and subsequent conversion of degraded forest to oil palm plantation (Wilcove et al, 2013). There is a substantial body of evidence showing that the community composition of many species in Southeast Asian rainforest changes with logging and conversion to oil palm dominated landscapes (Danielsen et al, 2009;Fitzherbert et al, 2008;Foster et al, 2011), including abundant tropical meso-predators such as anurans (Faruk et al, 2013). Furthermore, there is some evidence that interactions of other ecologically important groups such as ants are altered by conversion to oil palm plantations .…”
Section: Introductionmentioning
confidence: 99%